P-490 Patient Care Guidance: Development of a unique tool for fertility clinics based on best practice evidence. (30th June 2022) - Baccino, G; Dejewski, J
Abstract: Study question: How can fertility clinics be encouraged to implement evidence-based person-centred care? Summary answer: To help fertility clinics provide holistic care to their patients a multidisciplinary team developed a user-friendly, evidence based practical guidance. What is known already: Despite wide evidence about the benefits of person-centred care for patients seeking fertility treatment, this is not systematically implemented in most fertility clinics. Study design, size, duration: The aim was to develop evidence-based practical guidance on person-centred care for fertility clinics. A multidisciplinary team collaborated to developed person-centred care guidance for fertility clinics over a 12-month period. Participants/materials, setting, methods: A group of 18 stakeholders, including:15 fertility experts, 2 patient associations and 1 quality manager reviewed and summarised evidence relating to the needs of fertility patients to guide the implementation of person-centred care in fertility clinics. It was specially designed to fulfil the needs of different countries' legislation and cultural contexts. Main results and the role of chance: This collaboration resulted in a unique and practical evidence-based tool to help fertility clinics implement best practice in person-centred care. It includes a range of topics such as: the importance of a patient care system in ART; benefits of patient-centered care for patients, staff, and the clinic; ways to communicate information to patients; informing about fertility treatment options; fertility awareness; men's needs; emotional support; benefits of a mentor program; how to support to staff; exit strategies; needs of patients seeking cross-border care; the fertility clinic' online communication; engaging patients in good and safe choices; and also how to care about patients undergoing a gamete donation treatment. Limitations, reasons for caution: Despite the large number of topics required to support on fertility clinics, high impact topics were prioritised in the first phase of the guidance document – which will be updated periodically. Wider implications of the findings: This guidance offers added value to fertility clinics and patients. The authors were able to adapt scientific evidence into a practical and user-friendly guidance that allows all staff to understand the concept of patient-centred care, the roles, responsibilities, actions that can be taken to improve patient experience, outcome and care. Trial registration number: NO